Sosialisasi Deteksi Dini Kanker Payudara Di Bhayangkari Polres Pelabuhan Makassar - Naomi Malaha; Nur Febrianti; Dewi Sartika; Fitriani Fitriani; Lusyana Aripa; Yuliana Sri Widhihastuti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Breast cancer is the most common type of cancer in women in Indonesia, with incidence rates increasing every year. Breast cancer is also the second highest cause of cancer deaths in women in Indonesia after cervical cancer. So, it is necessary to raise awareness about breast cancer and the importance of prevention and early detection efforts, in order to reduce the risk of death from the disease. The objectives obtained by carrying out this activity, namely providing information and knowledge and increasing women's awareness to take action to detect breast cancer early through breast self-examination so that they can recognize early signs of breast cancer. The method of activities carried out in this service is in the form of counseling with the lecture method using leaflet and video media. Education is proven to be effective in increasing understanding of breast cancer prevention in participants and also very enthusiastic about the material because they get new knowledge. Therefore, it is necessary to increase socialization and training activities to the head of women, especially PKK mothers of Makassar Port Police about early prevention of breast cancer.